The Interplay of Intellectual Capital And Earnings Management on Corporate Valuation: Insights From Financial Services Companies - Aulizza Abdul Fanni (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2025)
Rising competition in the financial services industry is becoming more fierce, leading firms to explore innovative strategies to improve their market valuation. Within this context, intangible assets like intellectual capital and financial reporting methods such as earnings management have garnered more focus. This study investigates how intellectual capital performance and earnings management affect the corporate valuation, as proxied by Tobin’s Q, in the financial services companies listed on the IDX. It also identifies which elements of intellectual capital most significantly enhance the valuation. Out of the complete population, a sample of 69 companies was selected annually that fulfilled the criteria for selective sampling and further examined using panel data analysis. The results indicate intellectual capital positively influences firm value in a significant manner. The significant contributions arise primarily from the capital aspects of human and relational resources, whereas the structural component does not significantly impact firm value. This situation is regarded as favorable, though it is not yet optimal. In contrast, earnings management shows no statistically significant impact on firm value. These findings suggest that intellectual capital is a key value driver, whereas earnings management is not a reliable strategy for enhancing firm value in the context examined.